GB Virus C/Hepatitis G Virus Isolates in Japanese Haemophiliacs and their Origins - Toyoda, Hidenori; Fukuda, Yoshihide; Hayakawa, Tetsuo; Takamatsu, Junki; Saito, Hidehiko; Okamoto, Hiroaki (Thrombosis and Haemostasis, 1998)
Japanese haemophiliacs have been at high risk for infection with parenterally-transmissible viruses through the use of blood products, especially imported ones. Recently, novel transfusion-transmissible virus, GB virus C (GBV-C)/hepatitis G virus (HGV) were isolated. We investigated the origin and route of transmission of GBV-C/HGV isolates in haemophiliacs in Japan. GBV-C/HGV RNA was measured by nested reverse transcription polymerase chain reaction in 91 Japanese haemophiliacs. Phylogenetic analysis and genotypic grouping of GBV-C/HGV isolates in Japanese haemophiliacs were performed based on sequences in the 5’ untranslated region, and the characteristics were compared with those of reported isolates. GBV-C/HGV infection was present in 19 of 91 haemophiliacs (20.9%). Sequence analysis showed that 15 of the 19 isolates (78.9%) showed sequence similarity to a group in which mainly West African isolates have been reported. The other 4 isolates (21.1%) showed sequence similarity to Asian isolates. None of the GBV-C/HGV isolates showed sequences similar to those generally found in isolates from USA and Europe. The majority of GBV-C/HGV isolates found in Japanese haemophiliacs who are considered to have been infected by imported blood products were similar to those detected in West Africa.